Quality Assurance of Nursing Performance in Surgical Wards - Allah, bushra; AI-Gersha, Khalida; Al-Gailani, Saieb (Iraqi National Journal of Nursing Specialties, 2007)
Objective: The study deafs with nursing performance in the surgical wards in general hospital atBaghdad city.Methodology : A descriptive evaluation design using, observational method was carried out. Nonprobability (purposive) sample of (151) nurses was selected for the study and comprised all nurses whoworked in general surgical wards in the four health sectors( Rusaffa , Al-Karkh, Al-Yarmok, Medicalcity health sector) at time of collecting the data. A check list questionnaire was constructed by theresearcher for the purpose of the study; it is composed of (2) major parts, part (I) is concerned withsocio-demographic data and the second part is composed of two minor parts thev concerned withavailability of equipment and nursing performance. Validity of the questionnaire was determinedthrough panel of experts. Reliability of the questionnaire was determined through computationcorrelation coefficient of (93.3) was statistically acceptable.The data were analyzed through theapplication of the descriptive data analysis approach and the inferential statistics. Results : The findingsof the study indicated that more than half of the sample (66.2%) was male, the majority of the sample(71.52%) were in group (25-30) year. Most of the sample (29.8%) was training course graduates. Thehigher percentage (58.3%) has no training session after ward.Findings of the study had pointed that there were severe shortages in availability of equipmentrelated to patients admission procedure, preoperative and postoperative nursing care procedures.Theresults also revealed that the nurses performance were inadequate related to some nursing proceduressuch as admission procedure, preoperative nursing care procedure and postoperative nursing procedure.The findings of the study has approved that there was significant relationship between nursingperformance and demographic variables, Such as gender, age, level of education, training session.